The world food outlook - Mitchell, Donald 1947-; Ingco, Merlinda D. 1959-; Duncan, Ronald C. 1936- (Trade and development, 1997)
Modern day Malthusians warn that Malthus will ultimately be right: the world will be less and less able to feed itself as populations keep expanding and crop yields seem to have reached a peak. The authors of this volume believe that this pessimism is misplaced, and that there is in fact no worldwide food crisis. On the contrary, they show that the world food situation has improved dramatically over the past three decades: prices of agricultural commodities are at their lowest level in history in real terms and crop output is continuing to rise faster than population. This book provides a much needed and reasoned view on a subject that is too often treated emotionally. The important changes in the international food economy are considered in historical context and provide a basis for projections to 2010. The situation should continue to improve and food should become cheaper than it is today